Intellectual Property Rights in the Digital Disruption Era: A Normative Review of Copyright Protection - Anis Noviya (PT. Anagata Sembagi Education, 2025)
The era of digital disruption has significantly transformed the landscape of intellectual property, particularly in the realm of copyright protection. With the rapid evolution of digital technology, creative works are now more vulnerable to unauthorized use, duplication, and distribution across various online platforms. This normative legal research aims to analyze the adequacy and responsiveness of existing copyright laws in addressing the challenges posed by digital advancements. Utilizing a statute and conceptual approach, the study examines the current regulatory framework in Indonesia and compares it with international standards. The findings indicate that existing copyright laws are still limited in their ability to offer comprehensive protection in the digital age. Key issues include weak enforcement mechanisms, lack of digital monitoring systems, and outdated legal provisions that do not reflect technological realities. The study emphasizes the urgent need for legal reform that integrates digital-based enforcement tools and aligns national copyright regulations with global legal frameworks. Strengthening the legal infrastructure and improving public awareness are essential to ensure effective copyright protection in the era of digital disruption.